Assessment of seasonal influenza vaccine effectiveness in patients from a central Italy reference hospital: pitfalls and intricacies from a pilot case-control study - Katleen de Gaetano Donati; Simona Costanzo; Lara Campana; Marco Olivieri; Rosaria Santangelo; Maurizio Sanguinetti; Roberto Cauda; Licia Iacoviello (Epidemiology, Biostatistics and Public Health)
Objectives: Influenza vaccination protects high-risk populations from severe outcomes. We assessed the feasibility of testing influenza vaccine effectiveness against hospitalization with laboratory-confirmed influenza. Methods: All hospitalized patients with influenza-like illness within 14 days, were swabbed. Cases were positive at RT-PCR for influenza A/B. Results: AtRome “GemelliHospital” (Season 2011-2012) 104 patients were contacted and 62 recruited. Considering total sample and target group (n= 47, 76%), only 29% and 38% had been vaccinated. Eighteen patients were laboratory-conﬁrmed for influenza. Conclusions: RecruitedILI patients and prevalence of vaccinated subjects were less than expected. Larger numbers are warranted to study vaccine effectiveness against severe influenza outcomes.